2007
DOI: 10.1080/10241220801895840
|View full text |Cite
|
Sign up to set email alerts
|

The effect of steric bulk on coordination sphere geometry for BiCl3complexes with bulky heterocyclic imidazolethione ligands

Abstract: The synthesis and characterization of three new complexes, BiCl 3 (mipit) 2 , BiCl 3 (emit) 2 and BiCl 3 (mnpit) 2 are reported where emit ¼ 1-ethyl-3-methyl-2(3H)-imidazolethione; mnpit ¼ 1-methyl-3-(1-propyl)-2(3H)-imidazolethione;mipit ¼ 1-methyl-3-(2-propyl)-2(3H)-imidazolethione. X-ray crystallographic results are reported for the mnpit and mipit complexes whereas the structure of the emit complex is under reinvestigation because of disorder. BiCl 3 (mnpit) 2 crystallizes in a triclinic space group (P1) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The S1-Bi1-O1 angle of 176.2(2)° deviates slightly from linearity. The coordination behavior of 1,3-dialkylimidazole-2-thiones toward BiCl 3 and resulting mononuclear and dinuclear complexes have been described by Williams et al [11]. The authors reported dinuclear compounds of the type [Bi(imt) 2 (µ-Cl)Cl 2 ] 2 , from imt ligands and from a N-substituted imidazole-2-thione ligand [9], which are structurally related to complex 2.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The S1-Bi1-O1 angle of 176.2(2)° deviates slightly from linearity. The coordination behavior of 1,3-dialkylimidazole-2-thiones toward BiCl 3 and resulting mononuclear and dinuclear complexes have been described by Williams et al [11]. The authors reported dinuclear compounds of the type [Bi(imt) 2 (µ-Cl)Cl 2 ] 2 , from imt ligands and from a N-substituted imidazole-2-thione ligand [9], which are structurally related to complex 2.…”
Section: Resultsmentioning
confidence: 87%
“…The authors reported dinuclear compounds of the type [Bi(imt) 2 (µ-Cl)Cl 2 ] 2 , from imt ligands and from a N-substituted imidazole-2-thione ligand [9], which are structurally related to complex 2. It is interesting to note that the two M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 11 identical Bi-S bond distances of 2.703(2) Å in complex 2 are considerably shorter than those reported in these works, where they range from 2.750(1) to 2.937(1) Å. Although shorter Bi-S bonds have been observed in scorpionate tris(imidazole-2-thione) complexes of Bi(III) [17,19,20], those observed in 2 are in the lower range for this bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12] With an increasei nt he orbitals ize of the chalcogens (O 2p, S3p, Se 4p, and Te 5p), the stability of the corresponding ketones gradually decreases owing to improper orbitalo verlap with carbon (C 2p). [13] Rationally,e xamples of chalcogenone monomers progressivelyd ecrease from Ot oT e. As am atter of fact, monomeric tellurones are extremelyr are, [14,15] whereas similar oxonesa nd thionesa re quite common in nature and in synthesis laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] With an increasei nt he orbitals ize of the chalcogens (O 2p, S3p, Se 4p, and Te 5p), the stability of the corresponding ketones gradually decreases owing to improper orbitalo verlap with carbon (C 2p). [13] Rationally,e xamples of chalcogenone monomers progressivelyd ecrease from Ot oT e. As am atter of fact, monomeric tellurones are extremelyr are, [14,15] whereas similar oxonesa nd thionesa re quite common in nature and in synthesis laboratories.…”
Section: Introductionmentioning
confidence: 99%